Factors Associated with Respiratory Complaints in Mill Concentrating Workers Pt. Leighton Contractor Indonesia Site Pt. Freeport Indonesia - Shofiyyah, Shofiyyah; Thamrin, Yahya; Wahyu, Atjo (Journal of Neonatal Surgery, 2025)
Background: Respiratory complaints, such as coughing, phlegm, dyspnea, wheezing, and chest pain, can be an early sign of lung damage and are one of the occupational diseases caused by exposure to pollutants in the workplace environment. Objective: This study aims to analyze the factors associated with respiratory complaints in workers in the concentrating mill factory. Method: This study employed a cross-sectional analytic design. The sampling method used was total sampling, involving all 62 workers from the population. Data were analyzed using the chi-square test with the help of the SPSS software. Results: There is a relationship between working period (P = 0.002), length of work (P = 0.000), use of PPE (P = 0.000), and smoking status (P = 0.002) and respiratory complaints in workers in the mill concentrating, while there is no relationship between age (P = 0.136) and nutritional status (P = 0.115) and respiratory complaints in workers in the mill concentrating/ Conclusion: Respiratory complaints in workers may result from prolonged work duration, substandard PPE use, and smoking habits. While age and nutrition show little effect, maintaining regular nutritional intake supports overall health